Factors Associated with Hepatitis C Knowledge before and after an Educational Intervention among Vietnamese Americans - Sunmin Lee; Shumenghui Zhai; Guo (Yolanda) Zhang; Xiang S. Ma; Xiaoxiao Lu; Yin Tan; Philip Siu; Brenda Seals; Grace X. Ma (Clinical Medicine Insights: Gastroenterology, 2015)
Background Hepatitis C virus (HCV) is a major cause of chronic liver disease and cancer. Vietnamese Americans are at high risk of HCV infection, with men having the highest US incidence of liver cancer. This study examines an intervention to improve HCV knowledge among Vietnamese Americans. Study Seven Vietnamese community-based organizations in Pennsylvania and New Jersey recruited a total of 306 Vietnamese participants from 2010 to 2011. Results Average knowledge scores for pretest and posttest were 3.32 and 5.88, respectively (maximum 10). After adjusting for confounding variables, age and higher education were positively associated with higher pretest scores and having a physician who spoke English or Vietnamese was negatively associated with higher pretest scores. Additionally, after adjusting for confounding variables, household income, education, and having an HCV-infected family member significantly increased knowledge scores. Conclusions Promotion and development of HCV educational programs can increase HCV knowledge among race and ethnic groups, such as Vietnamese Americans. Giving timely information to at-risk groups provides the opportunity to correct misconceptions, decrease HCV risk behaviors, and encourage testing that might improve timely HCV diagnosis and treatment.